Exploring visitors' motivations and perspectives on festival tourism in Northern Cyprus: economic, cultural and social dimensions in a post-pandemic era - Altun, Ozlem; Kiraz, Sila; Saydam, Mehmet Bahri (Emerald Group Publishing Ltd, 2024)
PurposeThis research aims to investigate the motivations and perspectives of festival tourism in Northern Cyprus, emphasizing its economic, cultural, and social impacts in the post-pandemic era.Design/methodology/approachA qualitative approach was used to find out themes from semi-structured face-to-face interviews with twenty visitors who attended various festivals in North Cyprus.FindingsThe results of this research uncover that festivals considerably contribute to the local economy by attracting tourists, which boosts sales for local businesses and promotes traditional Cypriot cuisine. Additionally, festivals play a crucial role in preserving and promoting cultural heritage through traditional music, dance, and crafts, fostering community engagement and cultural exchange. The study also identifies key challenges and opportunities, such as the need for improved marketing strategies, enhanced infrastructure, and sustainable practices to mitigate environmental impacts.Originality/valueThis study provides a comprehensive analysis of festival tourism in Northern Cyprus, offering novel insights into its economic, cultural, and social impacts while proposing innovative strategies to enhance its post-pandemic recovery and sustainability.
Keywords: Festival tourism; Event; Cultural; Social; Sustainability